Uncovered Interest Parity - Isard, Peter (Washington, D.C. : International Monetary Fund, 1991)
This note provides an overview of the uncovered interest parity assumption. It traces the history of the interest parity concept, summarizes evidence on the empirical validity of uncovered interest parity, and discusses the implications for macroeconomic analysis. The uncovered interest parity assumption has been an important building block in multiperiod and continuous time models of open economies, and although its validity is strongly challenged by the empirical evidence, its retention in macroeconomic models is supported on pragmatic grounds, at least for the time being, by the lack of much empirical support for existing models of the exchange risk premium.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet